The portable Darwin - Darwin, Charles (Penguin Books, 1993)
The collections of Darwin's writings includes five chapters from The Origin of the Species; excerpts from The Voyage of the Beagle, The Descent of Man, and The Variation of Animals and Plants under Domestication; scientific papers, travel writings, and letters.